Menabung dengan Kreativitas: Program Pembuatan Celengan dari Bahan Bekas di MI Nurul Yaqin Desa Mangunsari - Sepanya Situmorang; Fika Uswatun; Sudiyono Sudiyono (Jurnal Bina Desa, 2026)
Financial education or financial literacy is a basic skill that everyone should have. Good financial management should be taught to children as early as possible so that they can understand and apply it. The introduction of the basic concepts of saving and making piggy banks is the goal of giat 9 unnes students. The flow of socialization activities includes preparation and planning, preparation of materials, implementation of activities and evaluation at MI Nurul Yaqin Mangunsari village. With this socialization, it is expected that children can apply the concept of saving in their daily lives.